Pulmonary functions in pseudoexfoliation syndrome. (15th May 2018) - Batur, Muhammed; Seven, Erbil; Tanrıkulu, Merhamet; Ekin, Selami; Tekin, Serek; Yasar, Tekin
Abstract: Objectives: It is well‐known that pseudoexfoliative material deteriorates iris dilatation function. This material was also found in lung tissue. The aim of the study was to evaluate pulmonary function in patients with pseudoexfoliation. Methods: This prospective study included 60 pseudoexfoliation syndrome patients without any pulmonary diseases and 52 age‐ and gender‐matched controls without any pulmonary diseases. Patients were asked about their cigarette use and the presence of any systemic diseases such as diabetes mellitus, arterial hypertension and asthma. All cases underwent full ophthalmologic and general medical examinations including pulmonary auscultation and pulmonary posterior‐anterior X‐ray. Pulmonary function tests were used for evaluation of pulmonary function. FVC, FEV1, FEV1 %, FEV1 /FVC and saturation values were recorded. Results: Mean age was 67.1 ± 8.8 (44‐82) years in the pseudoexfoliation group and 63.8 ± 9.4 (43‐82) years in the control group ( P > .05). Mean FEV1 was 1.60 ± 0.62 in the pseudoexfoliation group and 1.84 ± 0.61 in the control group ( P = .036). Mean FEV1 % was 70.65 ± 23.89 in the pseudoexfoliation group and 83.46 ± 17.83 in the control group ( P = .002). Mean FEV1 /FVC ratios were 0.72 ± 0.15 in the pseudoexfoliation group and 0.77 ± 0.11 in the control group ( P = .043). No statistically significant differences were found between the groups for FVC, saturation or cigarette use. Conclusion: These results suggest that there is decline in some pulmonary functions in pseudoexfoliation syndrome.